Wprowadzenie do rozważań o krytyce słuchowiskowej - Pleszkun-Olejniczakowa, Elżbieta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 1998)
The essay deals with the differences between literary and radio criticism (for instance, unlike a book, a radio-drama is not a commodity; its addressee is unclear, the reader does not have the slightest doubt as two WHO is the author of a book, which is not the case with a radio-drama; unlike radio-programmes, a publishing season as a whole is not subject to criticism, etc). Extracts from various types of reviews are presented in the second part of the article, which also contains a tentative introductory categorization. The reviews fall into the following categories: season recapitulation reviews; short introductory information given before particular radio-programmes; such information enriched by a short purely critical text; texts containing the author's biography and a summary of the work; the fullest reviews including, besides the above-mentioned elements, the phonic shape of a radio-drama. The essay ends with an annexe, containing a list of radio critics and short biographical notes.